THE PROSPECTS OF INTERNATIONAL TRADE FOR INDONESIAN PALM OIL COMMODITIESTOWARD GLOBAL MARKET DEMAND - Dwi F. Moenardy; Martin Purnama Chandra; Mohd Haizam Saudi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This study aims to discuss the Indonesian palm oil commodity in meeting global market demands. The benefits of palm oil are not only used as raw material for various products in the world but also as a source of renewable energy or biofuel that can replace fossil fuels which are predicted to be scarce. Indonesia, the largest producer of palm oil understands this and realizes that there are no similar competitors so that it can take advantage of these conditions for the market share of palm oil commodities on a global scale. The method used by the author is descriptive method, with data collection techniques and case studies as a basis. The limitation of the problem in writing is to discuss the prospects for palm oil through the high demand of the global market.